Mechanize or exit farming? Multiple‐treatment‐effects model and external validity of adoption impacts of mechanization among Nepalese smallholders - Takeshima, Hiroyuki (Wiley, 2018)
The future of smallholders in developing countries is becoming increasingly uncertain in the face of rising farm wages. The custom‐hiring of tractors, in which tractor owners provide non‐owner farmers with land preparation and transport services for fees, has spread among smallholders in Asia, including Nepal. However, estimating the adoption impacts of agricultural mechanization by smallholders is complex as we must also take into account smallholders’ options to exit farming. We investigate this issue by applying multinomial logit inverse‐probability weighting and sample selection panel data methods to data on smallholders in lowland Nepal. Our results are generally consistent with the hypothesis that smallholders who are likely to benefit more from adopting tractors are also more likely to exit farming. Where smallholders are less likely to exit farming, the use of tractors through custom‐hiring may help smallholders on average to earn greater total and agricultural incomes. However, where they are more likely to exit farming, the ability of custom‐hired tractors to sustain smallholder farming systems may become weaker. The results also offer insights into how the external validity of technology adoption impact evaluation may be affected in some settings.